Salient Beliefs About Earthquake Hazards and Household Preparedness - Becker, Julia S.; Paton, Douglas; Johnston, David M.; Ronan, Kevin R. (Risk analysis, 2013)
Prior research has found little or no direct link between beliefs about earthquake risk and household preparedness. Furthermore, only limited work has been conducted on how people's beliefs influence the nature and number of preparedness measures adopted. To address this gap, 48 qualitative interviews were undertaken with residents in three urban locations in New Zealand subject to seismic risk. The study aimed to identify the diverse hazard and preparedness‐related beliefs people hold and to articulate how these are influenced by public education to encourage preparedness. The study also explored how beliefs and competencies at personal, social, and environmental levels interact to influence people's risk management choices. Three main categories of beliefs were found: hazard beliefs; preparedness beliefs; and personal beliefs. Several salient beliefs found previously to influence the preparedness process were confirmed by this study, including beliefs related to earthquakes being an inevitable and imminent threat, self‐efficacy, outcome expectancy, personal responsibility, responsibility for others, and beliefs related to denial, fatalism, normalization bias, and optimistic bias. New salient beliefs were also identified (e.g., preparedness being a “way of life”), as well as insight into how some of these beliefs interact within the wider informational and societal context.